Kevin R. Cox (comp). Urbanization and conflict in market societies. Chicago : Maaroufa Press, Inc. 1978. 251 p. - Herzog, Lawrence A. (El Colegio de México A.C., 1983)
Kevin R. Cox (Comp.), Urbanization and Conflict in Market Societies, Maaroufa Press, Inc. Chicago, 1978.